Optimalisasi Media Sosial sebagai Alat Promosi untuk CAMP Anak Langit - Dani Hamdani; Ucu Nugraha; Endang Amalia (JURPIKAT (Jurnal Pengabdian Kepada Masyarakat), 2024)
In the era of globalisation and advances in information technology, social media has spread to all levels of society, including young people. CAMP Anak Langit (Creative and Motivated People) is a community that focuses on developing the potential creativity and motivation of young people. However, CAMP Anak Langit still faces challenges in promoting its activities and programmes optimally. Optimising social media as a promotional tool can help as an effective solution. Social media is not only a form of interaction, it is also an efficient means to expand reach, raise awareness, and gain support from the wider community. The implementation of community service activities with a focus on optimising social media as a promotional tool is expected to contribute in advancing CAMP Anak Langit and empowering the creative potential and motivation of its members.